2018
DOI: 10.3390/en11030654
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Parameter Optimization Model for the Evaluation of Shale Gas Recovery Enhancement

Abstract: Although a multi-stage hydraulically fractured horizontal well in a shale reservoir initially produces gas at a high production rate, this production rate declines rapidly within a short period and the cumulative gas production is only a small fraction (20-30%) of the estimated gas in place. In order to maximize the gas recovery rate (GRR), this study proposes a multi-parameter optimization model for a typical multi-stage hydraulically fractured shale gas horizontal well. This is achieved by combining the resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(26 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…ese findings were slightly different from previously observed findings in other studies which showed that as the PEG 6000 concentration increased, drug release also increased for immediate release tablets [27]. is limited effect of PEG 6000 on the drug release might be due to the fast disintegration nature of the tablets and micronized form of glibenclamide used in this study [28].…”
Section: In Vitro Drug Releasecontrasting
confidence: 99%
See 1 more Smart Citation
“…ese findings were slightly different from previously observed findings in other studies which showed that as the PEG 6000 concentration increased, drug release also increased for immediate release tablets [27]. is limited effect of PEG 6000 on the drug release might be due to the fast disintegration nature of the tablets and micronized form of glibenclamide used in this study [28].…”
Section: In Vitro Drug Releasecontrasting
confidence: 99%
“…ODTs. e selection was based on the comparisons of several statistical parameters including the coefficient of variation (CV), multiple correlation coefficient (R 2 ), adjusted multiple correlation coefficient (adjusted R 2 ), and predicted residual sum of squares (PRESS), provided by Design-Expert ® software [28]. Accordingly, the quadratic model and linear model were selected for friability and disintegration time, respectively.…”
Section: Response Model Selection a Mathematical Model Was Selected mentioning
confidence: 99%
“…The initiation of hydraulic fractures and the stress distribution of shale reservoirs are also affected by the uniaxial compression strength (UCS) of shale, while cracks begin to extend when the stress intensity reaches or exceeds the fracture toughness of the shale [47,48]. The more organic matter content in shale with a lower UCS, the easier for cracks to initiate and extend forward during fracturing [49].…”
Section: Uniaxial Compression Failure Modesmentioning
confidence: 99%
“…Current mainstream technologies available for commercial development of shale gas are horizontal drilling plus hydraulic fracturing, which can largely enhance reservoir permeability [2][3][4][5][6]. After hydraulic fracturing, the gas production rate is dramatically enhanced in the short term but this high production rate drops quickly in the longer term [7]. For conventional gas reservoirs, single hydraulic fracturing mainly generates great-scale fractures from the preexisting fractures.…”
Section: Introductionmentioning
confidence: 99%